1986
DOI: 10.1007/bf01849225
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance of two copper IUDs: Nova-T and MLCu375

Abstract: A comparative randomized trial was made of two intrauterine contraceptive devices: Nova-T and MLCu375. The IUDs were used by 637 and 606 women, respectively, for one year, unless the device was removed earlier. The reasons for IUD removal were analyzed after one year using the life-table method. Statistically significant differences were found in expulsion and removal for bleeding and/or pain rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 7 publications
(4 reference statements)
1
7
1
Order By: Relevance
“…De Castro and Anguiano [4] reported that, with the ML Cu375, both the accidental pregnancy rate (0.4%) and the expulsion rate (1.5%) were lower than the rates in this study. However, Thiery and associates [5] reported an accidental pregnancy rate of 0.4% and an expulsion rate of 2.4% with the ML Cu375.…”
Section: Discussioncontrasting
confidence: 80%
“…De Castro and Anguiano [4] reported that, with the ML Cu375, both the accidental pregnancy rate (0.4%) and the expulsion rate (1.5%) were lower than the rates in this study. However, Thiery and associates [5] reported an accidental pregnancy rate of 0.4% and an expulsion rate of 2.4% with the ML Cu375.…”
Section: Discussioncontrasting
confidence: 80%
“…No differences in the pregnancy rates were found when we changed the IUD design with the same load of copper [1,3,12]. We conclude that the contraceptive effectiveness of the high-load copper IUD could be due to the ability of copper to prevent estrogen and progesterone from exerting their full effects on the endometrium during IUD use.…”
Section: Discussionmentioning
confidence: 64%
“…This fact could be responsible for the important decrease in pregnancy rates when women use high-load IUDs [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important was the addition of copper to the IUD itself, which led to a reduction in IUD size, along with reduced pain, bleeding and expulsions [11. Later, the amount of copper in the IUD was further increased to more than 300 mm ~, which reduced the pregnancy rate three or four times [2]. Studies of different shapes have concluded that the TCu and ML IUD are the most effective and popular IUDs.…”
Section: Introductionmentioning
confidence: 98%